The Ambiguity of Employment Relationship in Indonesia's Gig Economy: A Study of Online Motorcycle Taxi Drivers - Muhyiddin, Muhyiddin; Annazah, Nur Siti; Henriko Tobing, Henriko; Habibi, Nugroho; Fauziyah, Fahimah; Harsiwie, Riesa Istiqamah Putri (Jurnal Ketenagakerjaan, 2024)
The rise of the gig economy in Indonesia, driven by digital platforms such as Gojek and Grab, has created significant employment opportunities through online motorcycle taxis (ojek online). However, the employment relationship between digital platforms and online motorcycle taxi drivers remains ambiguous. Currently, no explicit regulation defines the status of gig workers within Indonesia's legal framework. The absence of recognition as formal employees leaves these workers in precarious conditions, devoid of social security, minimum wage guarantees, and collective bargaining rights. This policy paper reviews existing regulations, evaluates international approaches, and identifies the benefits and challenges of unregulated gig work in Indonesia. Comparative benchmarks from Spain, the United States, and Malaysia highlight potential solutions to balance worker protection and platform flexibility. This study proposes a hybrid employment relationship that integrates core labor protections while maintaining work flexibility. Key regulatory components include social security access, algorithm transparency, and dispute resolution mechanisms. Short-term (1-year) and medium-term (5-year) strategies are outlined to achieve comprehensive regulations for Indonesia’s gig economy. Ultimately, this research provides actionable policy recommendations for the Indonesian government to establish fair and sustainable employment relations in the digital era.